A Critical Reflection on Neoliberalism. Issue 4 (1st October 2020) - Vahabi, Mehrdad; Mohajer, Nasser
Abstract: In this interview, we first scrutinise the meaning of classical liberalism and its revision by New liberalism in the twenties as social liberalism to demonstrate the conceptual confusion in using the term 'neoliberalism' as an economic doctrine. We then discuss the emergence of American neoliberalism as developed by the economic and law departments of the University of Chicago in the seventies notably by the Monetarist school. The anti-inflation program of Milton Friedman and Washington consensus provide a particular version of neoliberalism as economic policy. However, neoliberalism also pertains to a transitional, and non viable post-Fordist accumulation regime that has collapsed by 2007-2008 crisis. We also demonstrate the opposition against neoliberal economic policy not only by left critics but also by many right and center economists, politicians and scholars. Finally, we refute the idea of considering the political economy of the Islamic Republic of Iran (IRI) as neoliberal. Borrowing Vahabi's theoretical framework, we characterise parallel institutions and foundations as political capitalism with the predominance of predatory para-statal sectors. The limits of reformist and transformationalist discourses are revisited in light of political economy of the IRI, and the need for a social and political revolution is concluded.